Vibrationally resolved absorption and emission spectra of rubrene multichromophores : temperature and aggregation effects - Gao, Fang (2011)
We present a theoretical study on the temperature-dependent absorption and photoluminescence spectroscopy of rubrene multichromophores by combining the time-dependent long-range-corrected density functional theory with the exciton model. The spectra of rubrene multichromophores up to heptamers are calculated, and the effects of exciton−phonon coupling and temperature on the photophysical properties of both H- and J-aggregated oligomers are addressed. It is found that the spectral behavior of rubrene aggregates is very much dependent on aggregation details. As the temperature increases, higher excitonic states become populated, and low-energy dark states in H-aggregated oligomers become observable gradually while the peak intensities near the 0−0 transition decrease for J-aggregated oligomers.